Antitesis Terhadap Malaikat, Musa dan Elia: Studi Analisis Tekstual "Andres Duo" dalam Kisah Para Rasul 1:10 - Andris Kiamani (Predica Verbum: Jurnal Teologi dan Misi, 2025)
The purpose of this research article is to understand the true figure of the two men in white mentioned in Acts 1:10. From previous research, there are two interpretations in translating the figure of the two men. Firstly, not a few have the interpretation that the figure is an angel. Secondly, another interpretation states that the figures are Moses and Elijah. If so, who is the real figure of the two men dressed in white mentioned in Acts 1:10? To answer this question, this research is conducted through a specific and comprehensive study. Based on the use of interpretative qualitative methods in accordance with the hermeneutic process, this article concludes based on the use of masculine nouns in ancient Greek that the two men in white were two adult males in comparison to the other sex or in relation to a woman or her partner, which at the same time the existence of the two men shows that the event was not just a spiritual experience of the disciples, but had a concrete physical dimension that was very real. This research has revealed an antithesis to the Angel, Moses, and Elijah in Acts 1:10.